Assessment of the Graduates of the Medical Career on the Acquisition of Professional Competencies during their Training - Ferrero, María Laura (2021)
Introduction: Competence-based medical education emerges as an effective pedagogical strategyfor solving problems and making decisions about the future professional. In our country, resolution1314/07 of the Ministry of Education defines basic professional skills to acquire during the career.Students' assessment of what they have learned is a source of information to evaluate the process,which is crossed by multiple individual and contextual factors that affect their training. The objectiveof this work is to analyze the assessment of graduates about their training process and the acquisitionof basic skills, and their relationship with certain individual and contextual characteristics.Methods: The assessment of 342 graduates of the medical career of the Faculty of Medical Sciences ofthe UNLP was analyzed. Information was collected on the following variables: Socio-demographiccharacteristics, academic trajectory, work history and assessment of the training received for each ofthe competencies defined by Ministry of Education.Results: Competencies valued as not fully acquired according to general practitioner profile. Thecomparative analysis showed a significant relationship between the assessment of competencies notfully acquired and students that work during their college career or according to the profession oftheir parents.Conclusion: results obtained will allow, to support the review of medical competencies demandedby the National Ministry of Education and to propose alternatives to improve the training processof those most vulnerable students.